Development of the Information Storage Micromodule for Spacecrafts with LATCH-UP Effect Protection - S. Litvinenko, R.; V. Prokofiev, I. (International Journal of Engineering and Technology, 2018)
Exposure to outer space ionizing radiation places high demands on the circuits for fault tolerance. The issue of information safety on storage devices is especially acute in conditions of high radiation. Within the framework of the project on development of constructive and technological methods of creation of miniature data storage drives for onboard equipment for space purposes, the study of the radiation effects influence on the operation of memory chips and methods of counteracting these effects is carried out.Â Â